Выделение устойчивых переменных нелинейных систем с использованием метода дополнительных функций - Ковалев, А.М. (Доповіді НАН України, 2010)
Поставлена i розв’язана задача вилучення стiйких змiнних для нелiнiйної автономної системи диференцiальних рiвнянь iз вiдомою функцiєю Ляпунова зi знакосталою похiдною. Методом додаткових функцiй функцiя Ляпунова перетворена до вигляду, який дозволяє видiлити стiйкi змiннi та здобути iнтеграл. Обмiрковано зв’язок цих питань з методом в’язки iнтегралiв Четаєва. Розглянуто рухи твердого тiла з маховиком i гiроскопа Горячева–Чаплигiна. The problem of the selection of stable variables is formulated and solved for a nonlinear autonomous system of differential equations with a known Lyapunov function with the derivative of constant sign. With the help of the method of additional functions, a Lyapunov function is transformed to select the stable variables and to obtain an integral. The connection between these questions and the Chetaev method of integrals bundles is discussed. The motions of a rigid body with rotor and a Goryachev–Chaplygin gyroscope are considered.